Global Comparability of Financial Reporting Under IFRS Does Comparability Enhance Value Relevance of Earnings Across Countries? - De Luca, Francesco; Phan, Ho-Tan-Phat. (Cham : Springer International Publishing : Imprint: Springer, 2022)
The globalization of financial markets worldwide has progressively pushed toward simultaneous globalization of accounting information. Thus, during the last 50 years, categories of preparers, users, and regulators have devoted their efforts to support the global comparability of financial reporting aiming at favoring the comparison of corporates' financial performances at a cross-country level. In the same vein, IASB, national standard setters, and jurisdictions have participated in and given momentum to this process. At the same time, academic research has followed this process and tried to build a theoretical framework to address the related issues, to assess the impact on preparers, users, and regulators, while defining hindrances and obstacles to the comparability of financial reporting especially in an IFRS environment. In this context, this book reviews research studies on the comparability of financial reporting at a global level as well as highlights empirical analyses that demonstrate the extent to which global comparability has been achieved, and how it enhances value relevance of earnings across countries. It also looks at the cross-country investors' perspectives by shaping the empirical analysis to provide further insights on the role of the "Big Four" auditing services in enhancing the comparability of earnings. The book provides an original contribution to the current debate about the comparability of financial reporting under IFRS and will be useful for researchers in the field.
1. Comparability as a driver of Financial Reporting Quality -- 2. Criticalities along the path to Global Comparability of financial reporting -- 3. The role of Auditing in Global Comparability of financial reporting -- 4. Cross-country Empirical Analysis on IFRS based financial reports -- 5. Conclusion.
Keywords: Financial statements; International business enterprises; Corporate governance; Accounting; Financial Reporting; International Business; Corporate Governance; Financial Accounting